Study on Formation Cross-section of Singlet and Triplet Exciton in Organic Phosphorescent and Fluorescent Material - HUANG, JIN-ZHAO; LI, SHI-SHUAI; FENG, XIU-PENG; WANG, PEI-JI; ZHANG, ZHONG (Asian Journal of Chemistry, 2010)
In this study, the photoluminescence and electroluminescence device based on PVK [poly-(N-vinylcarbazole)] co-doped by Ir(ppy)3 [tris(2- phenylpyridine)-iridium(III)] and DCJTB (4-(dicyanomethylene)-2-tbutyl- 6-(1,1,7,7-tetramethyl-julolidyl-9-enyl)-4H-pyran) have been fabricated. According to the luminescence process and the changing spectrum of photoluminescence (PL) and electroluminescence (EL), the formation cross-section of singlet and triplet exciton were investigated and the value of the formation cross-section of triplet exciton in Ir(ppy)3 to that of singlet exciton in DCJTB is 9.